2020
DOI: 10.14202/vetworld.2020.2319-2325
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characterization and phylogenetic study of Indonesian cuscuses from Maluku and Papua Island based on 16S rRNA gene

Abstract: Background and Aim: Indonesian cuscuses are now becoming scarce because of the reduction of habitat and poaching. Further, molecular characterization of Indonesian cuscuses is still very lacking. This study aimed to determine genetic markers and phylogenetic relationships of Indonesian cuscuses based on 16S rRNA gene sequences. Materials and Methods: This study used 21 cuscuses caught from two provinces and 16 islands: 13 from Maluku and eight from Papua. Cuscus samples were taken by biopsy following ethics g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Many studies of such cuscus characterizations have been carried out. Based on the sequence of the 16S rRNA gene, the Indonesian cus- cus descended into two clades, known as the group of the genus Phalanger and the group of the genus Spilocuscus (Widayanti et al, 2020). The results of the phylogenetic tree demonstrated that S. maculatus is closely related to P. Gymnotis and that P. orientalis is closely related to P. urinus (Usmany and Kakisina, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies of such cuscus characterizations have been carried out. Based on the sequence of the 16S rRNA gene, the Indonesian cus- cus descended into two clades, known as the group of the genus Phalanger and the group of the genus Spilocuscus (Widayanti et al, 2020). The results of the phylogenetic tree demonstrated that S. maculatus is closely related to P. Gymnotis and that P. orientalis is closely related to P. urinus (Usmany and Kakisina, 2019).…”
Section: Introductionmentioning
confidence: 99%